Exploring relatives' perceptions of participation, ethics, and communication in a patient‐driven study for hereditary cancer variant reclassification. Issue 5 (9th January 2020) - Tsai, Ginger J.; Chen, Annie T.; Garrett, Lauren T.; Burke, Wylie; Bowen, Deborah J.; Shirts, Brian H.
Abstract: Effective communication of genetic information within families depends on several factors. Few studies explore intra‐familial communication of variant of uncertain significance (VUS) results or active collaboration between family members to classify VUS. Our qualitative study aimed to describe the experiences of individuals asked by family members to participate in the FindMyVariant study, a patient‐driven family study which aimed to reclassify a clinically identified familial VUS in a hereditary cancer gene. We collected feedback from 56 individuals from 21 different families through phone interviews and written correspondence, transcribed the interviews, and performed thematic analysis on all text. We describe themes from three main topics: participation, ethical considerations, and study impacts. Participation in the FindMyVariant study, defined as returning a sample for targeted genotyping, was motivated by convenience and a desire to help the family, oneself, and science. Relatives were generally responsive to invitations to participate in FindMyVariant from another family member. Those who declined to participate did so due to concerns about research program confidentiality rather than family dynamics. No major ethical issues arose in response to the patient‐driven study structure, and no major changes in stress and anxiety, medical care, or behavior occurred. Participation in patient‐driven familial VUS classification studies has a neutral or positive impact on family health communication. While it is important to design studies to minimize familial coercion, intra‐familial confidentiality breaches, and misinterpretation of genetic results, these were not major concerns among relatives in this study. Clinicians and laboratories may consider encouraging familial communication about genetic variants using family members as liaisons.